ORAL TRANEXEMIC ACID WITH TRIPLE COMBINATION CREAM (FLUCINOLONE+HYDROQUINONE+TRETINOIN) VERSUS TRIPLE COMBINATION CREAM ALONE IN TREATMENT OF MELASMA - Basit, Anam; Rahman, Atiya; Uddin, Rehan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Melasma is an acquired cutaneous disorder characterized by hyperpigmentation of the face predominantly affecting the areas exposed to direct sun light. The triple combination cream, i.e., a mid-potency corticosteroid (Fluocinolone acetonide 0.01%), a retinoid (Tretinoin 0.05%), and Hydroquinone 4% is one of the widely used topical medicament for melasma treatment world over. Tranexamic acid is another agent found to be effective in melasma treatment when used topically, intra-lesionally or orally. This study has been conducted to compare mean decrease in Melasma Area Severity Index (MASI) score when tranexamic acid is combined with triple combination cream versus triple combination cream alone for melasma treatment. Methods: A randomized controlled trial was conducted in a tertiary care hospital of Pakistan. Sixty-three patients of melasma who met the inclusion criteria and gave written informed consent for the study were enrolled. These patients were randomly divided into 2 treatment groups. Group A was given triple combination cream and oral tranxemic acid while Group B was given triple combination cream for duration of 8 weeks. Severity of melasma was assessed by MASI, which was calculated at baseline and at the end of week 8. Mean decrease in MASI score was calculated in both groups and statistically analysed employing SPSS 20. Results: Sixty patients, 30 in both groups, completed the study. Study participants were predominantly female (81.67%), with mean age of 30.46±6.24 years in group A while 31.90±4.53 in group B. No statistically significant difference was noted in both treatment groups for mean decrease in the MASI score (6.4933±4.38358 in group A compared to 5.7833±5.04251 in the group B; p-value 0.56). Conclusion: The addition of oral tranexamic acid did not contribute significantly in decrease in MASI score when used in combination with topical triple regimen. It may have a role as an adjuvant to topical triple combination cream.